Comparative analysis of reproductive health knowledge and practices of female college students in Xinjiang medical and non-medical majors in 2023 - Xayida Aini; Maerhaba Abudurexit; Aliye Aili; Nadire Maiming; Yilijiang Tuhongjiang; Weiju Hu; Xiaofei Liang; Asimuguli Kelimu (Scientific Reports)
Abstract This study aimed to understand the reproductive health status and knowledge of female college students in Xinjiang, comparing medical and non-medical majors. 625 female students from three universities were surveyed using a self-designed questionnaire. 26.6% had menstrual disorders, 51.8% had dysmenorrhea, and only 12.8% had undergone gynecological exams. Medical students had better knowledge than non-medical students. There are differences in female college students’ cognition of reproductive health concept, common physiological knowledge and problems between men and women, sexual diseases and contraceptive knowledge. The results of binary Logistic regression analysis show that knowing the concept of reproductive health [OR(95%CI):1.912(1.210,3.251)] is a protective factor affecting the current situation of reproductive health. The present situation of female college students’ reproductive health needs to be further improved, and many unhealthy hygiene habits still exist in their daily life, and their awareness of self-care needs to be improved. Schools and health departments should pay attention to the popularization of reproductive health education and promote the improvement of reproductive health status of female college students.